THE DARK SIDE OF THE RED LIGHT - Meneguzzi, Nelci Lourdes Gayeski; Tonél, Rodrigo; Gagliardi, André; Dilkin, Rogério De Almeida (Salão do Conhecimento, 2017)
Interdisciplinary theme among the areas of education, law and social communication